2018
DOI: 10.1139/apnm-2017-0457
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral corticomotor responses are confined to the homologous muscle following cross-education of muscular strength

Abstract: Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties in any format or medium for personal research or study, educational, or not-for-profit purposes without prior permission or charge, provided the authors, title and full b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
(127 reference statements)
1
19
0
Order By: Relevance
“…In the context of cross-education and bilateral transfer, several acute studies that have used TMS have shown increased CSE (Muellbacher et al 2000;Hortobágyi et al 2003;Perez and Cohen 2008;Howatson et al 2011;Frazer et al 2017), decreased SICI (Perez and Cohen 2008;Leung et al 2015), and decreased interhemispheric inhibition (IHI) (Perez and Cohen 2008;Howatson et al 2011) in the iM1. While some structural changes occur within several motor areas (Ruddy et al 2017;Pruitt et al 2016), experimental findings from chronic cross-education studies support a mixture of increased CSE (Hendy et al 2015;Kidgell et al 2011;Kidgell et al 2015) and a decrease in cortical inhibition (SICI, IHI and silent period duration) (Hortobágyi et al 2011;Hendy et al 2012;Kidgell et al 2015;Coombs et al 2016;Mason et al 2017) in the neural structures innervating the untrained limb.…”
Section: The Cortical Adaptations To Cross-education Are Dependent Upmentioning
confidence: 97%
See 4 more Smart Citations
“…In the context of cross-education and bilateral transfer, several acute studies that have used TMS have shown increased CSE (Muellbacher et al 2000;Hortobágyi et al 2003;Perez and Cohen 2008;Howatson et al 2011;Frazer et al 2017), decreased SICI (Perez and Cohen 2008;Leung et al 2015), and decreased interhemispheric inhibition (IHI) (Perez and Cohen 2008;Howatson et al 2011) in the iM1. While some structural changes occur within several motor areas (Ruddy et al 2017;Pruitt et al 2016), experimental findings from chronic cross-education studies support a mixture of increased CSE (Hendy et al 2015;Kidgell et al 2011;Kidgell et al 2015) and a decrease in cortical inhibition (SICI, IHI and silent period duration) (Hortobágyi et al 2011;Hendy et al 2012;Kidgell et al 2015;Coombs et al 2016;Mason et al 2017) in the neural structures innervating the untrained limb.…”
Section: The Cortical Adaptations To Cross-education Are Dependent Upmentioning
confidence: 97%
“…Sample size calculations were established on the average effect sizes for changes in the magnitude of strength transfer following a short-term unilateral strength training program and VT. Using previous cross-education data in healthy untrained adults (Mason et al 2017), we estimated that 10 participants in each group would provide at least 80% power (95% confidence interval) to detect a 18% cross-transfer of strength and 16% transfer of VT performance using a repeated measures design (G*Power 3.1.7 software).…”
Section: Participants and Sample Size Calculationsmentioning
confidence: 99%
See 3 more Smart Citations